PENGARUH KUALITAS PRODUK, E-PROMOTION TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE GOODS DEPT MELALUI BRAND IMAGE - Andreas Purna C, 13.05.51.0120 (Students Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of direct and indirect product quality, e-promotion and brand image as an intervening variable on purchase decisions. The population of this research is the consumer products The Goods Dept in Semarang city and Yogyakarta city who had been shopping throught online store www.thegoodsdept.com . The total sample 100 respondents with purposive sampling. Data obtained by the questionnaire. This research variable product quality (X1), e-promotion (X2), brand image (Z), and purchase decision (Y). Data analysis with statistical analysis descriptive and path analysis. The result of the research indicated that product quality (X1) and e-promotion (X2) directly influence purchase decision . variable product quality (X1) and e-promotion (X2) influence indirect purchase decision. The result of the path analysis show that the product quality (X1) and e-promotion (X2) impact on the purchase decision through the brand image. The conclusions from the study is the product quality, e-promotion and brand image as variable intervening influential directly and indirectly of the purchase decision. Was recommended to parties The Goods Dept to improve the quality of their products, by means of the process selection tighter. In e-promotion let parties The Goods Dept able to increase innovation and creation at the time offer their product online. Keyword : Product Quality, E-promotion, Brand Image, and Purchase Decision